2017
DOI: 10.1038/s41598-017-07226-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrative whole-genome sequence analysis reveals roles of regulatory mutations in BCL6 and BCL2 in follicular lymphoma

Abstract: The contribution of mutations in regulatory regions to tumorigenesis has been the subject of many recent studies. We propose a new framework for integrative analysis of genome-wide sequencing data by considering diverse genetic information. This approach is applied to study follicular lymphoma (FL), a disease for which little is known about the contribution of regulatory gene mutations. Results from a test FL cohort revealed three novel highly recurrent regulatory mutation blocks near important genes implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(46 citation statements)
references
References 76 publications
(97 reference statements)
7
38
0
Order By: Relevance
“…Finally, RPL39L 45 is involved in cancer stem cell self-renewal and hypoxia response. These results are concordant with other reports of non-coding regulatory mutations driving gene expression changes in B-cell lymphomas [46][47][48] .…”
Section: Discussionsupporting
confidence: 93%
“…Finally, RPL39L 45 is involved in cancer stem cell self-renewal and hypoxia response. These results are concordant with other reports of non-coding regulatory mutations driving gene expression changes in B-cell lymphomas [46][47][48] .…”
Section: Discussionsupporting
confidence: 93%
“…For example, many recurrent mutated regions in cancer genomes have been found to overlap with CTCF binding sites, showing a possible selection for these mutations ( Katainen et al, 2015 ; Lochovsky et al, 2015 ; Piraino and Furney, 2017 ). In addition, disruption of FOX TF binding sites in the BCL6 promoter have been reported in follicular lymphoma using an integrative approach that identifies functional regulatory mutation blocks ( Batmanov et al, 2017 ). Interestingly, both the creation and disruption of binding sites for the same TFs have been linked to cancer.…”
Section: Prediction Of Non-coding Snvs With High Functional Impactmentioning
confidence: 99%
“…Batmanov et al [ 4 ] performed whole-genome sequencing in follicular lymphoma (FL) and found three novel highly recurrent regulatory mutation blocks near BCL6 and BCL2, genes known to be important in FL development. They also found the transcription factors whose binding may be disturbed by these mutations: disruption of the FOX-family near the BCL6 promoter results in reduced BCL6 expression.…”
Section: Biology Of Lymphomamentioning
confidence: 99%